PPI and researcher perspectives of islet transplantation therapy for type 1 diabetes - Peter M. Jones; Sarah Gatward; Lesley Beadle; Amanda Panizza; Clare Blaydon‐Ellis; Sara Caxaria; Aidan Cruddace; Christine Deal; Ranna Patel; Alexander Silverstein; Lydia F. Daniels Gatward; Tzu‐Wen Hong; et al. (Diabetic Medicine, 2026)
Abstract Aims Islet transplantation offers the potential of a cure for type 1 diabetes ( T1D ), but the limited availability of human donor islets means that this therapy is currently only available to a small group of people with T1D who have intractable hypoglycaemia. The shortage of donor human islets has driven extensive research efforts to generate human islets from pluripotent stem cells ( SC ‐islets), and current protocols are producing SC ‐islets which are showing promising results in early clinical trials. As part of our T1D Grand Challenge research programme, we set up a Patient and Public Involvement ( PPI ) Steering Group with a diverse range of members with lived experience of T1D to interact with us and provide advice. The aim of this study was to explore how perceptions of human islet transplantation differ between people with lived experience of T1D and diabetes researchers. Methods To determine how perceptions of human islet transplantation may differ between people with lived experience of T1D and researchers, two islet transplant recipients recounted their experiences to members of the PPI group and the science researchers. Results We subsequently asked both groups for individual, anonymised responses to the presentations, and we here present an analysis of that survey. Conclusions Overall, this exercise highlights different approaches to islet/ SC ‐islet transplantation between people with lived experience of T1D and basic science diabetes researchers. This emphasises the continued need for open lines of communication between the two groups so each can benefit from the other's experience.